Здійснення права приватної власності на окремі види нерухомого майна за законодавством України - Лисенко, Андрій Миколайович; Лисенко, Ірина В'ячеславівна; Гаряєва, Ганна Михайлівна (Харківський національний університет внутрішніх справ, 2020)
Проаналізовано проблеми здійснення права приватної власності на нерухоме майно за законодавством України. На підставі дослідження конституційних і цивільно-правових норм, а також наукових праць із цієї тематики окреслено загальні засади та принципи реалізації власником своїх майнових прав щодо нерухомого майна, яке йому належить. Оскільки майнові права всіх суб’єктів правовідносин є не лише основою економічного розвитку всього суспільства, а й потужним фактором становлення кожної особистості в нашій державі, створення, ухвалення та застосування справедливих норм здійснення права приватної власності буде запорукою гармонійного соціально-економічного підґрунтя для кожного громадянина нашої держави.

Our research analyzes the problems of the implementation of the right to private ownership of real estate in accordance with the legislation of Ukraine. Due to the study of constitutional and civil law norms, as well as a number of doctrinal studies on this topic, we determine the basic principles and grounds for the owner to exercise his property rights to his real estate. It is the property rights of all subjects of civil relations that are the basis for both the economic development of society and a powerful factor in the formation of every personality in our state. Therefore, it will be fair to say that the need for the adoption, and especially the application of fair and reasonable norms of legislation, is a guarantee for the formation of economic protection of every citizen in our state and the formation of civil society in the whole. The study of the general theoretical foundations of the exercise of private property rights to real estate revealed the grounds for restrictions on private property rights. Taking into account the analysis of restrictions on the right of private property, their genesis, legal nature and content have been revealed; the legitimacy of certain restrictions on the right of private property has been substantiated. The general conclusion of the work is that the exercise of the right of private ownership of immovable property may be limited during the exercise by the owner of his property rights. The introduction of restrictions on the right of private ownership of immovable property in a state governed by the rule of law allows to coordinate the exercise of property rights between all subjects of civil legal relations and to ensure the protection of public interests.
Exercise of the private property right to certain types of real estate property under the law of Ukraine
Keywords: право приватної власності; власник; зміст права власності; права; свобода; інтереси суспільства; нерухоме майно; культурні цінності; private property rights; owner; content of property rights; rights; freedoms; public interests; real estate; cultural values